Penile shaft sinus: A sequalae of circumcision in urethral duplication - Lukman O Abdur-Rahman; AbdulRasheed A Nasir; John O Agboola; James O Adeniran (Indian Journal of Urology, 2009)
Urethral duplication (UD) is rare congenital anomalies with varied presentation. Careful clinical evaluation of children by specialist would enhance diagnosis, adequate management and reduce occurrence of complication. We present a 12-year-old boy with chronic post circumcision ventral penile sinus that was successfully managed for urethral duplication.